2023
DOI: 10.3390/ijms241612720
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Sphingolipids and Glucose Homeostasis: An Update

Sarah Ali-Berrada,
Jeanne Guitton,
Sophie Tan-Chen
et al.

Abstract: Sphingolipids are a family of lipid molecules produced through different pathways in mammals. Sphingolipids are structural components of membranes, but in response to obesity, they are implicated in the regulation of various cellular processes, including inflammation, apoptosis, cell proliferation, autophagy, and insulin resistance which favors dysregulation of glucose metabolism. Of all sphingolipids, two species, ceramides and sphingosine-1-phosphate (S1P), are also found abundantly secreted into the bloodst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that LDL-Cer inhibits insulin signaling in muscle, while HDL-S1P improves insulin signaling and enhances the function and survival of pancreatic cells (77,81,82). HDL-S1P and LDL-Cer exhibit contrasting effects on the progression of T2DM (76). Hence, the process of interconversion among these sphingolipid species is subject to strict regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that LDL-Cer inhibits insulin signaling in muscle, while HDL-S1P improves insulin signaling and enhances the function and survival of pancreatic cells (77,81,82). HDL-S1P and LDL-Cer exhibit contrasting effects on the progression of T2DM (76). Hence, the process of interconversion among these sphingolipid species is subject to strict regulation.…”
Section: Discussionmentioning
confidence: 99%